Pengembangan Aplikasi Kakas Bantu Untuk Menghitung Estimasi Nilai Modifiability Dari Class Diagram - Heru Apriadi; Faizatul Amalia; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the initial stages of developing a software, estimation of software size, effort, and cost is a very important issue for a developer and project administrator. Studies report that more than 90% of the total cost spent on software is caused by maintenance and evolution. Therefore the stakeholders expect that a software is built with the best design to improve efficiency and speed of work if there is a change in the software. Class diagram is one diagram created at the design stage of software development. Measuring the quality of the class diagram design of the software to be built can reduce revisions that may occur in the future. In the calculation of the estimated quality of this class diagram will be done by estimating the value of modifiability. To calculate the estimated value of the class modifiability estimation value, this diagram can be done manually, but it will take a long time if the calculation is done on a class diagram that has a large and complex number of classes and relations. Therefore, based on the problems that have been described, a solution is needed, namely the development of assistive tools to calculate the estimated modifiability of class diagrams automatically by using the calculation method using modifiability metrics. By making this system, it is expected to be able to resolve the problems that have been described. The research methods carried out in this study include the study of literature, data collection, needs analysis, design and implementation, testing and conclusions and suggestions. The system has also been tested by unit testing, integration testing, and functional validation testing to produce a value of 100% valid and testing the accuracy of the system by comparing the results of calculations with the system with manual calculations that produce a value of 100% valid.